Larangan Menimbun Harta Dalam Al-Qur’an (Analisis Metode Tafsir Maudhu’i Fazlur Rahman) - Barokah, Mabid; Alamsah, Johan; Ningrum, Anggun Puspita (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
AbstractThis study aims to examine the verses regarding the prohibition of hoarding wealth using Fazlur Rahman's maudhu'i (synthetic logic) interpretation method. This is because there is an editorial verse which discusses the characteristics of people who hoard wealth. To get answers to these problems, the author uses a qualitative type of library research method by analyzing content (content analysis) which results in the conclusion that there are verses that prohibit someone from hoarding wealth so that this causes a person to be negligent which is marked by not spending his wealth in the way of Allah as explained in His word in the Koran surah Al-Humazah (1-3), At-Takatsur (1), and At-Taubah (34-35).Keywords: Fazlur Rahman; Maudhu 'Method; Prohibition of Hoarding Goods. AbstrakPenelitian ini bertujuan untuk mengkaji ayat-ayat tentang larangan menimbun harta menggunakan metode tafsir maudhu’i (sintetik logic) Fazlur Rahman. Hal ini dikarenakan adanya redaksi ayat yang membahas mengenai ciri-ciri orang yang menimbun harta. Untuk mendapatkan jawaban dari permasalahan tersebut, penulis menggunakan metode kualitatif jenis library research dengan menganalisis isi (content analysis) yang menghasilkan kesimpulan bahwa ada ayat-ayat yang melarang seseorang untuk menimbun harta sehingga hal ini menyebabkan seseorang menjadi lalai yang ditandai dengan tidak menginfakkan hartanya dijalan Allah seperti yang dijelaskan pada firman-Nya didalam al-Qur’an surah Al-Humazah (1-3), At-Takatsur (1), dan At-Taubah (34-35). Kata Kunci: Fazlur Rahman; Larangan Menimbun Barang; Metode Maudhu’i.